The atypical Gaoligong orocline: Its geodynamic origin and evolution - Chiu, Yu-Ping; Yeh, Meng-Wan; Lee, Tung-Yi (Frontiers in Earth Science, 2023)
Various orocline systems around the India-Eurasia collision zone have long been recognized and studied. Different portions of the India-Eurasia boundaries represent various scales and models of oroclinal forming processes.The curvature from Eastern Himalayan syntaxis through East Burma to West Yunnan showed a unique convex curvature towards the mantle wedge. That is different from the concave Himalaya orocline. This unique geometry of the Gaoligong orocline showed N-S trending for the northern section and NE-SW trending for the southern section. This also marks the boundary between the Tengchong and Baoshan blocks along the Santaishan suture. Our structural reconstruction identified 5 deformation events of: the D1 km scale upright fold, which only effected the Neoproterozoic meta-sedimentary unit. The D2 recumbent fold, which only developed in the southern section. The D3 large-scale gently westward-inclined thrust folds, the D4 right-lateral shear belt, and D5 normal faults. Since D3 structure is the earliest event that shows penetrative foliation development along the orocline, we considered D1 and D2 as pre-orocline forming events. The geometry of the Gaoligong orocline is controlled by the distribution of the Ordovician basement between the Tengchong and Baoshan blocks. Both north and south sections experienced the same structural evolution since D3 (a fault-propagation fold system occurred between 40 and 28 Ma), D4 (steep right-lateral shear belt occurred between 28 and 15 Ma), and D5 (normal faults after 15 Ma). The curvature was first developed as the shovel-like top-to-the-NE thrust plane (S3) developed under amphibolite-facies conditions between 40 and 28 Ma. The following deformation events (D4 and D5) showed orocline parallel foliation development under lower metamorphic condition indicating the curvature of the Gaoligong orocline is not generated by further rotation along multiple deformation events. However, due to the lack of orocline parallel foliation development for S3, and the lack of proper position of the indenter, the Gaoligong orocline cannot be classified as a primary orocline nor a rotational orocline. The curved geometry is an interference pattern of topography relief to the shovel-like thrust plane that developed during D3. Our new reconstructed structural evolution concludes that the Gaoligong orocline is a “atypical” orocline.